J.M.G. Le Clézio : a concerned citizen of the global village - Moser, Keith A. (Lexington Books, 2013)
"This monograph represents the first comprehensive study of the multifaceted representations of the complex phenomenon of globalization in the diverse repertoire of the 2008 Nobel Laureate in Literature. This interdisciplinary investigation explores the original euphoria related to the ambivalent concept of the 'global village' and how this evaporated dream can perhaps be re-appropriated and redefined to create a better global society for both the human and Cosmic Other through the lens of Le Clézio's fiction"--Provided by publisher.